ALOCAÇÃO ÓTIMA DE CAPACITORES EM SISTEMAS DE DISTRIBUIÇÃO RADIAL, UTILIZANDO-SE ESTRATÉGIAS EVOLUTIVAS - Petinelli, Airton Egydio (2002)
Static reactive power sources, such as shunt capacitors, have been commonly used to provide reactive compensation in distribution systems, minimizing losses and keeping voltage levels within operational limits. Heuristic algorithms for capacitor placement have been proposed in several works. However, the majority of these approaches converge to a local solution. This dissertation presents a hierarchical evolution strategy-based approach for solving the optimal reactive sources placement in radial distribution systems. The approach is based on the (m+l)-EE paradigm, improved by mutations control and by two types of mutations: the classical Gaussian mutation and the Cauchy-based mutation. Discrete standard capacitor values with non-linear cost are considered. Constraints such as the maximum number of parallel banks and installations cost are included. Validation tests have been performed using a real industrial feeder.